Some Hydrazones of 2-Aroylamino-3-methylbutanohydrazide: Synthesis, Molecular Modeling Studies, and Identification as Stereoselective Inhibitors of HIV-1 - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (WILEY-V C H VERLAG GMBH, 2013)
In accordance with our antiviral drug development attempt, acylhydrazone derivatives bearing amino acid side chains were synthesized for the evaluation of their antiviral activity against various types of viruses. Among these compounds, 8S, 11S, and 12S showed anti-HIV-1 activity with a 50% inhibitory concentration (IC50)=123.8 mu M (selectivity index, SI>3), IC50=12.1 mu M (SI>29), IC50=17.4 mu M (SI>19), respectively. Enantiomers 8R, 11R, and 12R were inactive against the HIV-1 strain IIIB. Hydrazones 8S, 11S, and 12S which were active against HIV-1 wild type showed no inhibition against a double mutant NNRTI-resistant strain (K103N;Y181C). Molecular docking calculations of R- and S-enantiomers of 8, 11, and 12 were performed using the hydrazone-bound novel site of HIV-1 RT.
Keywords: Acylhydrazones; HIV-1; Molecular modeling; Non-nucleoside reverse transcriptase inhibitors; Stereoselective activity; REVERSE-TRANSCRIPTASE; NONNUCLEOSIDE INHIBITORS; ANTIMICROBIAL ACTIVITY; BIOLOGICAL-ACTIVITIES; COLORIMETRIC ASSAY; RIBONUCLEASE-H; IN-VITRO; DERIVATIVES; DISCOVERY; DESIGN